Cloud computing services and its Effect on tertiary education : Using google classroom - Alajmi, Qasim; Al-Nuaimy, Louay A.; Arul Jose, G. Jai; Mastan, Mohammed; Al-Sharafi, Mohammed Ali (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper examines the effectiveness of the Google Classroom App in learning for higher education institutions in Oman. The massive advancement in technology has contributed to changes in learning and delivery of learning resources in the classroom. Thus, it has saved the resources and reduced the cost of learning associated with the traditional learning model. The main goal of this paper is to investigate the students' perception about the cloud computing services accessibility, ease of use and usefulness by measuring the implementation effectiveness of Google Classroom as a mode of teaching. This study used quantitative approach mode to determine the effectiveness and the effect of using Google Classroom e-learning model, 225 completed questionnaires were analyzed using SPSS tool. Its evident that using Google Classroom for the learning is more effective and gained highest level of satisfaction among the learners. As a general result of this work students can use Google classroom in very comfortable and easy way really on the ability of online, remote, and time unconstrained conditions. The students also like to learn through the lecturer with the support of google classroom.